Peningkatan Hasil Belajar Siswa Dengan Menggunakan Model Pembelajaran Kooperatif Tipe STAD Dengan Bantuan Audio Visual Pada Mata Pelajaran Ilmu Pengetahuan Alam (IPA) Kelas V B SD Negeri 48 Barru - Sara, Ekawahyuni; Amin, Sulvahrul; Hasnini, Hasnini; Ramadani, Fitri (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2024)
This study aims to examine the improvement of learning outcomes of 20 students of class V B UPTD SDN 48 Barru, after the application of the STAD type cooperative learning model in Natural Science (IPA) learning with the help of audio visuals. The type of research used is Classroom Action Research (CAR) which in its implementation there are researchers and collaborators. The data collection technique in this study is a direct technique while the data collection tool uses observation sheets and question sheets. This study was carried out with two cycles, the average value obtained by students after taking the final test from cycle I was 57 to cycle II, namely 85 from the ideal value that could possibly be achieved 100. Thus it can be concluded that the use of the STAD type cooperative learning model with the help of audio visuals can improve the learning outcomes of class V B UPTD SDN 48 Barru students.